Lexical difficulties in translating oil and gas terms among non-native speakers - Badalova, Luiza (The Lingua Spectrum, 2025)
This article examines the lexical difficulties encountered by non-native speakers when translating oil and gas terminology. The study highlights the complexity and specificity of technical vocabulary in the oil and gas industry, where many terms have polysemous meanings, lack direct equivalents in other languages, or are culturally bound. The research analyzes common translation errors caused by lexical interference, false cognates, and insufficient professional background. Special attention is given to the challenges of translating abbreviations, collocations, and metaphorical expressions frequently used in petroleum engineering and energy-related texts. The paper emphasizes the importance of developing terminological competence and using specialized bilingual glossaries and corpora. It also suggests effective strategies for improving the accuracy of translation through context-based learning and interdisciplinary training. Additionally, the study underscores the role of technological tools such as digital terminology databases, machine translation systems, and corpus-driven platforms in enhancing lexical precision. The results demonstrate that mastering lexical nuances in this field is essential for achieving precision and clarity in professional communication, particularly in safety documentation, technical reports, and international collaboration.